Teachers' Efforts in Preventing Sexual Harassment in SDN 1 Watubelah Students - Fikriyah, Fikriyah; Putri Priatna, Dzela; Zulviani, Nita (Jurnal Edusci, 2024)
This study aims to find out how teachers' efforts in preventing sexual harassment in children in elementary schools. This study used qualitative research methods. In this type of descriptive research approach, the instruments in this study used interview instruments. The data collection techniques used were interviews and documentation. The subject of this study was one of the teachers at Watubelah 1 Public Elementary School. The results and discussion obtained from conducting this research are that teachers at SDN 1 Watubelah have made efforts to prevent sexual harassment of elementary school students. The efforts of teachers at SDN 1 Watubelah to prevent this are by 1) strict selection of teachers, 2) giving sexual education to children, 3) giving sanctions to perpetrators, and 4) creating a sense of security at school for students.